Structural Characterization and Surface Modification of Titanium Plates After Nd: YAG Laser Treatment - Bahloul,A. (2020)
Surface laser treatments of commercially pure titanium plates (CP-Ti grade 4) were performed in air using a Nd:YAG laser source of short pulse duration about 5 ns. Attention is drawn to the following laser-processing parameters: laser-power interaction time and surface of the irradiated zone. The morphology, structure and chemical composition of the formed layers were analyzed by different characterization techniques providing physico-chemical and structure information. The objective of this research was to study the influence of laser fluence on the composition of the CP-Ti grade 4. Additionally, it was pretended to evaluate the surface modification of obtained layers. The electrochemical response of modified surface in Ringer's physiological solutions at varying pH values was studied. Fretting test has been investigated in order to study the tribological behavior of the laser treated surface. Results showed that the laser treatments induce the insertion of light elements such as O2 and N2. Laser surface processing shifted the corrosion potential of CP-Ti grade 4 towards the noble side, as compared to the untreated one. After fretting tests, it was found that the steady friction coefficient was similar for all the layers, and quite lower than that measured for the untreated CP-Ti.